Pengaruh Work-Life Balance dan Stres Kerja terhadap Kinerja Pegawai Melalui Work Engagement Pada Pegawai Dinas Sosial Kabupaten Sragen - Cahya Charisma; Awalia Risky Ramadhani; Alfaridzi Bramantya Putra (Jurnal of Management and Social Sciences, 2026)
This quantitative, associative-causal study evaluates the contribution of work engagement in mediating the impact of work-life balance and work pressure on the productivity of personnel at the Sragen Regency Social Agency. Given the limited population size, a census method (total sampling) was applied to the entire workforce of 35 employees. Statistical results confirm that work-life balance significantly boosts work engagement, whereas work pressure shows no such association. Individually, neither work-life balance nor work pressure has a direct impact on performance outcomes. However, work engagement was found to be a key factor that significantly enhances employee performance. Sobel testing indicates that work engagement serves as a valid mediator for the work-life balance variable, but not for the work pressure variable. Therefore, organizational performance effectiveness at this agency is determined by strengthening employee work engagement, supported by a harmonious work-life situation.